ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN AIS PRODUCT DI KABUPATEN PURWOREJO - Kuswadi Rustam; Damar Eko Cahyono; Alief Indita Agustiani (Kajian Ekonomi dan Bisnis, 2025)
Ais Product is a household business engaged in bamboo and broom handicrafts. In this business the company is engaged in production and sales. The progress of Ais Product's business depends on the quality of the product, the planning of the products produced by the company must be truly in accordance with the needs of consumers. This is to be in accordance with the objectives of the company where the products produced can be accepted and in accordance with consumer needs and can satisfy consumers. This study aims to analyze the effect of Product Quality, Price, and Promotion on Purchasing Decisions on Ais Products. This study uses a method that is "descriptive" which is a research method by investigating the circumstances, conditions and situations in which the results are presented in the form of reports. The types of data used by the author are quantitative and qualitative data. The data source in this study uses primary data and secondary data. The primary data of the author obtains data from the results of the distribution of questionnaires (questionnaires) that are distributed and interviewed data about the effect of product quality, price, and promotion on purchasing decisions on Ais Product. Secondary data the authors obtained data from library studies and documentation obtained from company owners and sources related to the decision to purchase at Ais Product. Data analysis in this study uses Multiple Linear Regression with the SPSS program. The results showed that the variable ability of Product Quality, Price, and Promotion in explaining the purchase decision variable was 30,1% correctly based on the determination test, based on the t test it can be seen that the price variable did not influence and significantly influence the purchasing decision, while the product quality variable and promotion has a positive and partially significant effect on purchasing decisions. F test analysis is known that the F value of variable product quality, price, and promotion simultaneously have a significant effect on purchasing decisions on Ais Product.